On the relationship between Bayesian error bars and the input data density - Williams, C. K. I.; Qazaz, C.; Bishop, Christopher; Zhu, H. (Proceedings Fourth IEE International Conference on Artificial Neural Networks, 1995)
We investigate the dependence of Bayesian error bars on the distribution of data in input space. For generalized linear regression models we derive an upper bound on the error bars which shows that, in the neighbourhood of the data points, the error bars are substantially reduced from their prior values. For regions of high data density we also show that the contribution to the output variance due to the uncertainty in the weights can exhibit an approximate inverse proportionality to the probability density. Empirical results support these conclusions.